Skin markings methods and guidelines: A reality in image guidance radiotherapy era - Rathod, Shrinivas; Munshi, Anusheel; Agarwal, Jaiprakash (South Asian Journal of Cancer, 2012)
Abstract Preparation of site of radiation delivery is an important process in radiation treatment planning and plays a crucial role during a course of radiotherapy to achieve reproducibility of set-up and accuracy of treatment delivery. The preparation of treatment area is done by markings of field center, field edge or other reference point of planned field. Both non-invasive (marker pen, henna) and invasive methods (tattoo) are available for marking with limitations of each. Tattoo with a needle pricked at angle of 30° to 1-2 mm depth to create tattoo 2-3 mm diameter in size is an ideal procedure. Visibility, permanent nature, social-religious belief, and mobility of skin are one of the main concerns about tattoo. Tattoo removal can be done performed if desirable by patients by various modern ways, which will be esthetically available. Dermabrasion, cryotherapy, surgery, QSRL (Q-switched ruby laser) are common methods of tattoo removal. Esthetic dissatisfaction, allergy, dermatoses, keloids, infection, fanning/fading of tattoo are associated problems. In IMRT and IGRT treatment, delivery dependence on tattoo in reduced and use of surrogate markers including particularly for bony set-up and implanted markers (e.g. gold seeds) for tumor localization and treatment verification is increasing. However, these are complex procedures and require an expertise. Ease of set-up and less time required for tattooing are one of the main advantages of tattoo as compared to external or internal marker set-up. Tattoo still remains a crucial method of positioning, especially in developing countries and in palliative treatment settings.